Diverse Activators of the NLRP3 Inflammasome Promote IL-1ß Secretion by Triggering Necrosis - MARTIN, SEAMUS (My University, 2015)
The NLRP3 inflammasome is involved in caspase-1-dependent maturation of IL-1β in many contexts. A two-signal model has emerged for IL-1β maturation, with LPS providing “signal I” and diverse agents such as ATP, Nigericin, streptolysin O, uric acid crystals, and alum salts capable of acting as “signal II.” In the absence of signal II, pro-IL-1β is upregulated but typically fails to be processed or released. What unites signal II stimuli has been debated, with the ability to promote K+ efflux suggested as a common factor, but the mechanism of IL-1β release remains unclear. Here, we show that all examined inflammasome signal II agents triggered necrosis, which was highly correlated with their ability to promote IL-1β release. IL-1β secretion occurred in tandem with the release of many additional proteins and was confined to necrotic cells. Thus, signal II agents initiate inflammation by promoting necrosis-driven IL-1β release, suggesting that IL-1β represents an inducible danger signal.
Keywords: NLRP3 inflammasome